Principles of treatment of edentulous patients with overdenture prostheses on implants in the mandible - Chmiel, Grzegorz; Więckiewicz, Włodzimierz (Journal of Stomatology, 2017)
Abstract Introduction Prosthetic treatment of edentulous patients is often associated with patients complaining to low retention of the lower denture. The work presents the principles of dealing with such patients, ranging from their classification and proper planning of implant-prosthetic treatment. Aim of the Work Presentation of the rules during the treatment of edentulous patients with particular emphasis on the treatment with the use implants and overdentures to the edentulous mandible. Methods In planning treatment edentulous mandible taken into account: anatomical classification and division of edentulous arches by Misch, taking into account the number and location of intraosseous implants in the lower jaw, supporting overdentures. Results Application of the anatomical classification of toothless jaws and jaws according to Misch and the division taking into account the number and location of implants in the edentulous mandible, it facilitates the planning of treatment of edentulous patients with the use of a overdenture. Conclusions. 1. Planning the treatment according to the appropriate rules of conduct affects the durability of the treatment using a complete overdenture. 2. X-ray examination prevents complications during the procedure giving the possibility of appropriate categorizing and planning: the number of implants, their location and arrangement. 3. In the work, attention was paid to the preservation of the appropriate bone height in the anterior mandibular section necessary for implantation and retention of the future prosthesis. 4. The length of the rear bracket is determined by the distance A-P, the stress factors and the shape of the alveolar arch. 5. The universal locator system gives the patient great comfort during the chewing function by providing the denture with proper retention, stability and flexibility. Key words: Complete edentulism, implants, overdenture, attachments.